DETERMINANTS OF GOOD CORPORATE GOVERNANCE, COMPANY CHARACTERISTICS, AND ENVIRONMENTAL PERFORMANCE ON ISLAMIC SOCIAL REPORTING (ISR) DISCLOSURE - leniwati, driana; Fitriah, Dwi Nur; Harventy, Riska (Kompartemen : Jurnal Ilmiah Akuntansi, 2023)
The aim of this research is to analysis the influence of Good Corporate Governance, Company Characteristics, and Enviromental Performance on the disclosure of Islamic Social Reporting (ISR). The population of this research is the companies registered in Jakarta Islamic Index (JII) on year period 2015-2019. The sampling technique used was purposive sampling. The number of samples in this study were 45 samples. The data analysis techniques used were multiple linear regression, which were processed through SPSS version 25. The results showed that Good Corporate Governance as measured by Board of Commissioner Size and Public Ownership have a significant positive effect os ISR disclosure. Company Characteristics as measured by age of company had a significant effect while Type of Industry had not significant effect and Enviromental Performance had a significant effect. The result also proves that a company that stands in the community could not be separated from the social contract related to the norms that exist in society. The Legitimacy of the company is not only limited to financial reporting disclosure but ISR disclosure. It is important for the company to have a good relationship by interacting with the environment and the surrounding social which puts forward Islamic principles for their sustainability. This study also examines the Legitimacy and Stakeholder theory which is enhanced by Islamic principles by using the ISR index as a complement to the GRI index for information disclosure.Â Â